The geology of the Vaal Reefs Gold Mine, Western Transvaal - Jacob, Roger E (Rhodes University, Faculty of Science, Department of Geology, 1966)
Rocks forming part of the Main-Bird Series and the Kimberley-Elsburg Series of the Upper Division of the Witwatersrand System are found in the mine. The sequence studied starts with the Middle or MB 6 Zone of the Livingstone Stage followed by the Upper or MB 5 Zone. The Vaal Roof, forming the base of the Vaal Stage, rests disconformably on the older rocks. The Stage is subdivided into the Vaal Reef Zone, the Lower Vaal Zone, the Argillaceous Zone and the Upper Vaal Zone. The lower and upper contacts of the Argillaceous Zone are gradational. The Kimberley Stage follows unconformably and comprises the basal Gold Estates Conglomerate Zone, the Denny's Zone and the Gold Estates Zone. The overlying Elsburg Stage may be subdivided into the Bastard Zone and the Upper Elsburg Zone on lithological grounds. Most of the rocks are indurated quartz wackes with only a few orthoquartzite horizons such as the Denny's Zone and the immediate hangingwall of the Vaal Reef. Microscopically the rocks consist of detrital quartz and chert grains in a fine-grained sericitic to partly siliceous matrix which may constitute more than 50 per cent of the rock. Heavy minerals, such as zircon, chromite, rutile, leucoxone, pyrite, tourmaline, epidete, apetite and magnetite, occur in most of the zones. The Vaal Reef, the economic horizon, is of small-pebble, oligomictic conglomerate, often containing thucholite seams and granules, and varying in thickness from a mere parting to more than five feet. There appears to be a correlation between greater pebble size and higher ore grade but no correlation of sorting coefficients and gold value. The mineralogy of the Vaal Reef was studied by means of polished sections and heavy mineral concentrates. The minerals identified include gold, pyrite of several ages, pyrrhotite, chalcopyrite, uraninite, galena, brannerite, gersdorffite or cobaltite, skutterudite, linnacite, danaite, niccolite, pentlandite, magnotite, zircon, chromite, rutile, leucoxine, monazite, sphalerite, tourmaline, and fluorite. From a study of the silver content of gold in the Vaal Roof it is concluded that the variations in apparent fineness are a reflection of the composition of the gold in the original source rocks. There is a definite uranium-gold relationship in the Vaal Roof. With increase in grade the amount of U₃O₈ increases but the U₃O₈:AU ratio decreases. Use of these reations may indciate the payability in cases of incomplete core recovery.The intrusive rocks were studies in detail. Six types of intrusive rocks were found. From oldest to youngest those are quartz diabase (of three varieties), amygdaloidal diabase, ilmenite mela-microdiorite, mottled microdiorite, olivine lamprophyre and ankeritic beforsite, ranging in age from Lower Ventersdorp to post-Karroo. Most of the intrusives are highly altered due to the effects of regional metamorphism and deuteric alteration. Later formations, such as the Langgeleven and Allanridge Formations of the Ventersdorp System and the Black Roof and Dolomite Series of the Transvaal System, occur on the property. The various formations have been subjected to faulting and folding.
Keywords: Vaal reefs gold mine; Gold ores -- Geology -- South Africa -- Transvaal; Geology -- South Africa -- Transvaal